Advance and delay in the Holy Quran (Journal of the College of Basic Education, 2023)
Praise be to God who sent down the Book to His servant and made no crookedness for him, and prayers and peace be upon the Most HighLiwa al-Huda, our master Muhammad and his family and companions.And after...Several verses stopped me while I was reciting the Holy Qur’an, such as the Almighty’s saying: ((Allah, there is no god butHe is the Living, the Eternal, neither year nor sleep seizes Him.)) (Al-Baqara (255): And the Almighty said: ((Say: He is the one who brought youAnd He made for you hearing, sight, and hearts; little are you thankful)) (Al-Mulk 33: in terms of the order of its wordsAnd its connection with its meanings, and this was repeated in other verses, which prompted me to think about the reasons for presenting someprofanity and delaying others. Therefore, I decided to prepare a study on the introduction and delay in the Qur’anic expression, and what is related toI started examining them carefully, so I went back to the main books ofSources and reference for the delay of what our evacuation scholars agreed upon.The study was made in two chapters, the first chapter: in which it was researched:1- Quranic expression.2- The structure in the Quranic expression.The second chapter: Quranic presentation linguistically and rhetorically.Finally, I hope that I have succeeded in this endeavour, and if I fell short, God alone is perfect.The first chapter: Quranic expressionThere is no disagreement among scholars that the Qur'anic expression is unique in its loftiness and transcendence, and that it is the highest speech.Raise it, and that it dazzled the Arabs, so they could not condemn it and come up with the same, even though it challenged them more than once.The Qur’an has challenged the Arabs and then all of creation to come up with the same, and then told that they would not come up with the like of it even ifSome of them were at each other's back, so he first challenged them to come up with ten chapters like it, if they thought that he was fabricated.The Almighty said: ((Or do they say, “It is a fabrication?” Say, “Then produce ten chapters like it, and call on whomever you can besides God.If you are truthful, then if they do not respond to you, then know that it was revealed with the knowledge of God, and that there is no god but Him. So are youMuslims)) (Hud (14, 13).